1988
DOI: 10.2307/1911360
|View full text |Cite
|
Sign up to set email alerts
|

Rational Expectations and the Aggregation of Diverse Information in Laboratory Security Markets

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. The idea that markets might aggregate and disseminate information and also resolve conflicts is central to the literature on decentralization (Hurwicz, 1972) and rational expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
253
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 489 publications
(262 citation statements)
references
References 9 publications
8
253
0
1
Order By: Relevance
“…Smith (1776) and Hayek (1945) wrote of this and the concept was used to build the fundamental Theory of Rational Expectations and the Efficient Market Hypothesis -important pillars in modern economics. The ability of markets to assimilate information was empirically shown by Plott (1988). In the present study the process of assimilation will be described in terms of two components:…”
Section: What Are the Mechanisms Involved In The Information Assimilamentioning
confidence: 93%
See 1 more Smart Citation
“…Smith (1776) and Hayek (1945) wrote of this and the concept was used to build the fundamental Theory of Rational Expectations and the Efficient Market Hypothesis -important pillars in modern economics. The ability of markets to assimilate information was empirically shown by Plott (1988). In the present study the process of assimilation will be described in terms of two components:…”
Section: What Are the Mechanisms Involved In The Information Assimilamentioning
confidence: 93%
“…Plott and Sunder (1988) empirically showed that properly designed markets can indeed aggregate information. In their experiments, they defined three possible states of nature (X, Y and Z).…”
Section: Information Assimilation Capability Of Marketsmentioning
confidence: 99%
“…There are informed buyers who receive a noisy signal about the value of the asset. They adapt the design of Plott and Sunder (1988), originally developed to study information aggregation. Some traders receive private information that one of three possible states is not the true state.…”
Section: Market Microstructurementioning
confidence: 99%
“…They also look at selfmonitoring, which is a form of social awareness, and its connection to trading behavior. They consider the environment of Plott and Sunder (1988) with the addition that they allow short selling.…”
Section: Behavioral Traitsmentioning
confidence: 99%
See 1 more Smart Citation